2019
DOI: 10.1007/s42757-019-0009-y
|View full text |Cite|
|
Sign up to set email alerts
|

One-dimensional drift-flux correlations for two-phase flow in medium-size channels

Abstract: The drift-flux parameters such as distribution parameter and drift velocity are critical parameters in the one-dimensional two-fluid model used in nuclear thermal-hydraulic system analysis codes. These parameters affect the drag force acting on the gas phase. The accurate prediction of the drift-flux parameters is indispensable to the accurate prediction of the void fraction. Because of this, the current paper conducted a state-of-the-art review on one-dimensional drift-flux correlations for various flow chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…where the distribution parameter 0 C and the voidweighted mean drift velocity gj V are given by the Chexal-Lellouche correlation, which is independent of the flow pattern, applicable to a full range of thermodynamic conditions and geometries, and covers air-water counter-current flows. The Chexal-Lellouche correlation can be found in Hibiki (2019), Chexal et al (1997) and Chexal et al (1992) The values given by the Chexal-Lellouch correlation for the mean drift velocity gj V for countercurrent flow lead to counter-current flooding limit (CCFL) line well below the flooding line obtained from experimental results for air-water flow in inclined pipes reported in the literature (see Ghiaasiaan et al (1995)). This behavior was already mentioned by Takeuchi et al (1992), where the authors compare the drift velocity predicted by the Chexal-Lellouche correlation with the drift velocity predicted by others correlations and showed that the Chexal-Lellouch correlations gives smaller values for the drift velocity.…”
Section: Pipe Two-phase Flow Modelmentioning
confidence: 82%
“…where the distribution parameter 0 C and the voidweighted mean drift velocity gj V are given by the Chexal-Lellouche correlation, which is independent of the flow pattern, applicable to a full range of thermodynamic conditions and geometries, and covers air-water counter-current flows. The Chexal-Lellouche correlation can be found in Hibiki (2019), Chexal et al (1997) and Chexal et al (1992) The values given by the Chexal-Lellouch correlation for the mean drift velocity gj V for countercurrent flow lead to counter-current flooding limit (CCFL) line well below the flooding line obtained from experimental results for air-water flow in inclined pipes reported in the literature (see Ghiaasiaan et al (1995)). This behavior was already mentioned by Takeuchi et al (1992), where the authors compare the drift velocity predicted by the Chexal-Lellouche correlation with the drift velocity predicted by others correlations and showed that the Chexal-Lellouch correlations gives smaller values for the drift velocity.…”
Section: Pipe Two-phase Flow Modelmentioning
confidence: 82%
“…The liquid velocity U L,S within the liquid slug is determined using Eq. (19). The dispersed bubbles velocity within the liquid slug, U B , and the elongated bubble's nose translational velocity, U T , are determined from the drift kinematic law (see Table 1) similar to Eq.…”
Section: Kinematic Variablesmentioning
confidence: 99%
“…These improvements are developed due to the drift-flux sub-models, used for closing important parameters, present complex forms, and are often defined only based on empirical data, making difficult the analytical calculations for the model solution. These advances can be employed to handle more complex flow problems, i.e., in cases where more or less complicated mechanistic models are used, defining the parameters in the most physically correct way [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Gas-liquid two-phase flow in macro pipes are widely encountered in the industry as oil and gas production and transportation (Arabi et al, 2022, Boutaghane et al, 2023, nuclear power plants (Yeo, 2019;Hibiki, 2019), wastewater industry (Hundshagen et al, 2021) or in chemical and biochemical applications (Wang et al, 2021, Levitsky et al, 2022. These kinds of flows are also found in mini pipes such as those used in high-power electronic devices, heat exchangers and airconditioning systems (Hazuku et al, 2020) Due to the complexity of industrial installations, many parts of fluid transport systems are constituted by singularities, or fittings.…”
mentioning
confidence: 99%